2005
DOI: 10.3844/ajessp.2005.64.68
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration Characteristics of Granitic Residual Soil of Various Weathering Grades

Abstract: This study presents the result of a field study on the infiltration characteristics of cut a slope in granitic residual soil of various weathering grades. Granitic residual soil of weathering grade IV is found to have the highest infiltration rate. Water infiltration is found to increase from grade VI to IV and decrease from grade IV to grade III. Water infiltration is found to increase with the increase in soil porosity and void ratio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Results of the soil-moisture retention curves show variations with location of samples; a feature that is supported by a study involving the daily measurements of suction, moisture and temperature as well as rainfall, between 25/01/1992 and 12/05/1992 at depths of 30, 92 and 124 cm in morphological sub-zones IC, IIA, IIB and IIC of the weathering profile being discussed (Ali et al, 2005;. The study showed the value of suction to vary with depth and soil weathering grade; earth materials of sub-zone IC generally having the highest values of suction and those of sub-zone IIC having the lowest values.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Results of the soil-moisture retention curves show variations with location of samples; a feature that is supported by a study involving the daily measurements of suction, moisture and temperature as well as rainfall, between 25/01/1992 and 12/05/1992 at depths of 30, 92 and 124 cm in morphological sub-zones IC, IIA, IIB and IIC of the weathering profile being discussed (Ali et al, 2005;. The study showed the value of suction to vary with depth and soil weathering grade; earth materials of sub-zone IC generally having the highest values of suction and those of sub-zone IIC having the lowest values.…”
Section: Discussionsupporting
confidence: 53%
“…The weathering profiles are found in undulating to hilly and mountainous terrain and often considered to be equivalent with 'residual soils', though the term 'residual soil' should strictly only refer to that part of the weathering profile whose economic excavation would not require the use of explosives (United States Bureau of Reclamation, 1974). Weathering profiles furthermore, are usually located above zones of unconfined groundwater and they have thus been called "unsaturated soils" in geotechnical literature; such soils being characterized by the presence of suction (or negative pore-water pressures) (Ali et al, 2005). The relationship between moisture content and suction is expressed by the soil-water characteristic curve and is a fundamental relationship that needs to be determined in investigations of unsaturated soils (Vanapalli et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the infiltration rate of tuff is higher with the high degree of weathering; namely, the infiltration rate of moderately weathered tuff is 0.11 cm/second to 0.131 cm/second, highly weathered tuff is 0.168 cm/second to 0.412 cm/second, and completely weathered tuff is 0.346 cm/second to 0.512 cm/second. This phenomenon is in line with the results of research by Ali et al (2005), who found that the infiltration rate will be higher if the weathering grade is higher because the rock is destroyed. Consequently, its permeability and porosity become large.…”
Section: Landslide Slip Surfacesupporting
confidence: 90%